PLACENTA ACCRETA IN PRIMIGRAVIDA AT PERIPHERAL SETUP – A RARE CASE REPORT - CHOUREY, NIRAJ; RN, HIREMATH; YADAV, MANPAL SINGH; GHODKE, SANDHYA; KUMAR, DOBI SRAVAN (Asian Journal of Pharmaceutical and Clinical Research, 2021)
One of the risk factors for maternal mortality is morbidly adherent placenta (MAP) and accounts for 7–10% of maternal mortality cases worldwide. Placenta accreta is the most common type of MAP, while the other two types are placenta increta and placenta percreta. Placenta accrete accounts for 75–80% of MAP. Here, we present a case of 22 years old, primigravida with no known antenatal risk factors, diagnosed to have placenta accreta intraoperatively after delivering health baby. It is extremely rare for MAP to occur in a patient with no prior risk factors in a primigravida. Peripartum hysterectomy is the only option in a limited care facility with a hemodynamically unstable patient without a proper full-fledged blood bank facility. It is once again reiterated that bleeding from the vagina that does not slow or stop, drop in blood pressure and signs of shock are early signs of blood loss and should be investigated with great concern.